PENGARUH SENAM KAKI DIABETES TERHADAP SENSITIVITAS KAKI DENGAN PENGUKURAN IPSWICH TOUCH TEST (IPTT) - Ratnawati, Ratnawati; Jumari, Jumari; Papuke, Sri Susanti; Irbar, Irmariani (Klabat Journal of Nursing, 2025)
Background: Diabetes mellitus (DM) is a chronic disease frequently associated with peripheral neuropathy, which manifests as reduced foot sensitivity and increases the risk of diabetic foot ulcers and amputations. The Ipswich Touch Test (IPTT) is a simple and low-cost screening method that is feasible to implement in primary health care settings in Indonesia. Objective: This study aimed to analyze the effect of diabetic foot exercise on foot sensitivity measured using IPTT and to highlight its contribution to evidence-based nursing practice. Methods: A quasi-experimental pretest–posttest control group design was applied. Thirty patients with type 2 DM from Kota Timur Health Center were recruited through purposive sampling and divided equally into intervention (n=15) and control (n=15) groups. The intervention group performed supervised diabetic foot exercises three times per week for four consecutive weeks, while the control group received standard education only. Foot sensitivity was assessed using IPTT before and after the intervention. Data were analyzed with the Wilcoxon signed-rank test and the Mann–Whitney U test at a significance level of ρ<0.05. Results: The intervention group demonstrated a significant improvement in foot sensitivity (p<0.001), while the control group showed no clinically meaningful change (p=0.008). Posttest scores differed significantly between groups (p<0.001). Conclusion: Diabetic foot exercise effectively improves foot sensitivity in patients with type 2 DM as measured by IPTT. This study emphasizes IPTT as a practical screening tool in Indonesian primary care and supports its integration into national diabetes programs such as Prolanis. Latar belakang: Diabetes mellitus (DM) merupakan penyakit kronis yang sering menimbulkan komplikasi neuropati perifer berupa penurunan sensitivitas kaki. Kondisi ini meningkatkan risiko ulkus diabetikum hingga amputasi. Deteksi dini sensitivitas kaki menggunakan Ipswich Touch Test (IPTT) merupakan pendekatan sederhana yang relevan diterapkan di layanan primer Indonesia. Tujuan: Menganalisis pengaruh senam kaki diabetes terhadap sensitivitas kaki dengan menggunakan IPTT. Metode: Penelitian quasi-experiment dengan desain pretest–posttest control group. Sampel 30 pasien DM tipe 2 di Puskesmas Kota Timur, terdiri dari kelompok intervensi (n=15) yang melakukan senam kaki tiga kali seminggu selama empat minggu, dan kelompok kontrol (n=15) yang hanya menerima edukasi standar. Hasil: Uji Wilcoxon menunjukkan peningkatan signifikan sensitivitas kaki pada kelompok intervensi (p<0,001), sedangkan perubahan pada kelompok kontrol tidak bermakna secara klinis (p=0,008). Uji Mann–Whitney menunjukkan perbedaan signifikan skor posttest antar kelompok (p<0,001). Kesimpulan: Senam kaki efektif meningkatkan sensitivitas kaki pasien DM tipe 2. Penelitian ini berkontribusi terhadap praktik keperawatan berbasis bukti dengan menekankan IPTT sebagai alat skrining sederhana di layanan primer. Intervensi ini juga relevan diintegrasikan dalam program nasional seperti Prolanis.